Expression of Toll-like receptor (TLR) 2 and TLR4 in the livers of mice infected by Clonorchis sinensis - Chao Yan; Xiang-Yang Li; Bo Li; Bei-Bei Zhang; Jiang-Tao Xu; Hui Hua; Qian Yu; Zhuan-Zhuan Liu; Lin-Lin Fu; Ren-Xian Tang; Kui-Yang Zheng (Journal of Infection in Developing Countries)
Introduction: Clonorchis sinensis is one of the most important foodborne pathogens in humans, and can cause biliary diseases such as gallstones, cholecystitis, cholangitis, and cholangiocarcinoma. Toll-like receptors (TLRs) as sensors are crucial to initiating both innate and adaptive immune defenses against pathogens. However, little is known about the hepatic expression of TLRs of hosts induced by C. sinensis infection. Methodology: In the present study, the expression and distribution of TLR2 and TLR4 were investigated in a mouse model of clonorchiasis on days 28, 56, 84, and 112 post-infection (PI) using real-time quantitative reverse transcription polymerase chain reaction (PCR) and immunohistochemically staining, respectively. The levels of cytokines that are mediated by TLR2 and TLR4 were also evaluated using a cytometric bead array. Results: Results showed that the transcripts of TLR2 and TLR4 were upregulated on day 28 PI in C. sinensis-infected mice compared with non-infected ones (p < 0.01). In addition, their proteins were strongly immunohistochemically positive in the cytoplasm and membrane of endothelial cells, fibroblasts, and biliary epithelium cells of C. sinensis-infected mice. The levels of interleukin (IL)-4, IL-10, tumor necrosis factor alpha (TNF-α) and interferon gamma (IFN-γ) were increased with activation of TLR2 and TLR4. Conclusions: The expression of TLR2 and TLR4 is upregulated against C. sinensis infection, which suggests that TLR2 and TLR4 might be involved in immune responses during C. sinensis infection.